﻿Coleção de Vetores de Tripanosomatídeos (Fiocruz/COLVET) held at the institution Fiocruz Minas in Brazil: diversity of Triatominae (Hemiptera, Reduviidae) and relevance for research, education, and entomological surveillance - Raíssa N. Brito (Pensoft Publishers, 2021)
The Coleção de Vetores de Tripanosomatídeos (Fiocruz/COLVET), Minas Gerais, Brazil, stands out as one of the most important collections of blood-sucking triatomines, the vectors of Trypanosoma cruzi that causes Chagas disease. The aim is to describe the collection and the services it provides to support scientific research, educational activities, and entomological surveillance between 2013–2019.The data associated with the specimens held in Fiocruz/COLVET is available from the Sistema de Informação sobre a Biodiversidade Brasileira (SiBBr). These specimen metadata were analyzed and either tabulated or plotted on graph and maps. The records of services provided by the collection between 2013–2019 were also categorized and analyzed. There are 12,568 triatomine specimens deposited in the collection that belong to 77 species and 11 genera, from 15 American countries. Of the ~ 65 species of triatomines found in Brazil, 38 (57.6%) are present in the collection, including specimens from all biomes and all but three Brazilian states. The occurrence of Triatoma costalimai, Triatoma lenti, Rhodnius nasutus, and Panstrongylus lenti apparently collected beyond their known distribution ranges are reported and discussed. The collection provided 168 services, supporting educational activities (41.7%), scientific research (35.7%), and regional/national entomological surveillance of triatomines (22.6%). Between the years 2014 and 2020, the number of biological specimens deposited in the Fiocruz/COLVET repository increased from 4,778 to 12,568 triatomine specimens. In addition to its great value to biodiversity conservation, the collection is of great importance because of its support of research and educational activities, and contributions to entomological surveillance, and, therefore, to public health.